Studies on The Effect of Bio Fertilization on the Technological Characteristics of Some Egyptian Wheat Varieties - Dr. Abou El Enin; M.M; S.I, Dr. Abo-Remaila (Arab Journal for Sciences and Research Publishing, 2016)
Three pot experiments were carried out at Agric. Res. Station, Fac. Agric., Al-Azhar Univ. Nasr City during 2011/2012, 2012/2013 seasons, each one was to investigate the effect of four un mineral package for each N, P and K on quality of three wheat Egyptian varieties, such as, Sakha-93, Masr-1 and Banisweif-6. The N package were 75 kg N/fed (control), 75 kg N/fed + the twice cysteine spraying (each 150 ppm), 37,5 kg N/fed + bio N fertilizer (cerialen) + the twice cysteine spraying and 37,5 kg N/fed + bio N fertilizer (biogen) + the twice cysteine spraying. The p fertilizer packages were phosphorine, humic acid 6%, phosphorine+ humic 6% acid and control (without P). The K fertilizer package were Potassiumage, Banana ash 4%, Potassiumage + Banana ach 4% and control (without K fertilizer). On the other hand, a field experiment was applied in 2013/2014 session at El Klag region, Kaliobia Governorate, Egypt to confirm the result gaved from the pot experiments. However pot experiments were designed in complete randomizes design, the field experiment was in split plot design. Results showed significant differences between the three tested wheat varieties such as grain protein contents, wet and dry gluten content. Baniswif-6 gave grains quality characters higher than Sakha-93 and Masr-1 varieties in cache season under pot and field experiments. Technological properties were differed significantly between the studied nitrogen fertilizers packages treatments during the three growing seasons under pot or field experiments. In the second experiments, there were significant differences between the various phosphorus fertilizer packages treatments in both seasons under pot and field experiments. P4 and P3 treatments recorded the highest values of technological properties as compared with P1 treatment in the three seasons in pot or field experiments. The interaction effect between (var. X P. packages) showed that must of the studied characters were significant by the interaction between the two studied factors. Finally, in the third experiment, significant differences were observed between the four studied potassium fertilizers packages for all studied characters under pot and field experiment in both seasons, whereas K4 treatments gave the highest values of technological characters. Also K3 treatment ranked the second and produced the highest values of the previous traits in both seasons. Accordingly, the three wheat varieties showed highest responsibility to different N, P and K fertilizer packages in relation to some technological properties in pot or field experiments under these conditions